Int Adv Otol 2023
DOI: 10.5152/iao.2023.21560
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Compressed High-Intensity Radar Pulse and Tone Burst Stimulation in Vestibular Evoked Myogenic Potentials in Acute Peripheral Vestibular System Pathologies

Abstract: Background: It is ascertained that the compressed high-intensity radar pulse (CHIRP) is an effective stimulus in auditory electrophysiology. This study aims to investigate whether Narrow Band Level Specific Claus Elberling Compressed High-Intensity Radar Pulse (NB LS CE-CHIRP) stimulus is an effective stimulus in the vestibular evoked myogenic potentials test. Methods: A case-control study was designed. Fifty-four healthy participants with no vertigo complaints and 50 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 23 publications
(25 reference statements)
0
7
0
Order By: Relevance
“…In most studies, shorter P1 and N1 latency was obtained with the CHIRP stimulus in the cVEMP test. [15][16][17][18][19][20][21] Besides, Walther and Cebulla state that they found longer P1 and N1 latency with CHIRP stimulus. 22 Wang et al, Moinudeen et al, and Walther and Cebulla state that CHIRP stimuli produce higher amplitude values in the cVEMP test.…”
Section: Cvemps Results With Chirp Stimuli In Healthy Individualsmentioning
confidence: 96%
See 4 more Smart Citations
“…In most studies, shorter P1 and N1 latency was obtained with the CHIRP stimulus in the cVEMP test. [15][16][17][18][19][20][21] Besides, Walther and Cebulla state that they found longer P1 and N1 latency with CHIRP stimulus. 22 Wang et al, Moinudeen et al, and Walther and Cebulla state that CHIRP stimuli produce higher amplitude values in the cVEMP test.…”
Section: Cvemps Results With Chirp Stimuli In Healthy Individualsmentioning
confidence: 96%
“…CHIRP stimuli were compared with a 500 Hz tone burst. Bas [16][17][18]24,25 On the other hand, Walther and Cebulla indicated that there was no statistically significant difference in N1 and P1 latencies. 22 In all studies, higher N1-P1 wave amplitude values were reported in oVEMP.…”
Section: Ocular Vemp Results With Chirp Stimuli In Healthy Individualsmentioning
confidence: 97%
See 3 more Smart Citations